2018
DOI: 10.1159/000484029
|View full text |Cite
|
Sign up to set email alerts
|

New Medical Approach to Functional Dyspepsia, from Core Symposium 3, Japan Gastroenterological Association 2015–2017

Abstract: In the annual meeting of the Japan Gastroenterological Association (JGA), the scientific organizing committee selected the serial topics for the core symposium. One of the core symposia held during 2015-2017 was entitled "New medical approach to functional dyspepsia (FD)." In 2015, the subtitle of this symposium was "Helicobacter pylori gastritis and FD." In 2016, the subtitle of this symposium was "overlap with other functional GI disorders." In 2017, the subtitle was "therapeutic approach to FD." During thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Functional dyspepsia (FD) is a common functional gastrointestinal (GI) disease, and the global incidence of FD is 11.5%-29.2% [1,2]. ere are various options for treating FD, such as diet, prokinetic agents, acid suppression, fundic relaxers, tricyclic antidepressants, and psychological therapy, but the treatments are unsatisfactory [3].…”
Section: Introductionmentioning
confidence: 99%
“…Functional dyspepsia (FD) is a common functional gastrointestinal (GI) disease, and the global incidence of FD is 11.5%-29.2% [1,2]. ere are various options for treating FD, such as diet, prokinetic agents, acid suppression, fundic relaxers, tricyclic antidepressants, and psychological therapy, but the treatments are unsatisfactory [3].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, in Japan, new guidelines for FD were approved and also described that 24% of FD patients involved had chronic pancreatitis [15,18]. We have reported that 41% of FD patients with abnormalities of pancreatic enzyme were determined as ECP using EUS [19,20]. Ashizawa et al [21] have also reported that anti-acid-therapy-resistant FD involves FD patients concomitant with chronic pancreatitis.…”
Section: Introductionmentioning
confidence: 99%